Contextualization of Abdurrahman Wahid's humanistic da’wah in cases of violation of human rights in Indonesia - Rosidi, Rosidi; Musyafak, Najahan; Aisyah, Umi; Suslina, Suslina (Jurnal Ilmu Dakwah, 2023)
Purpose - Two things become the purpose of this paper. First, to describe Abdurahman Wahid's humanistic da’wah. Second, to read the contextualization of humanistic da’wah on Human Rights Abuse.Method - This paper applied Creswell's phenomenology in seeing the phenomena of Human Rights abuse. The data was taken from documents with humanistic da’wah and Abdurrahman Wahid's humanistic da’wah, along with human rights abuse cases that occurred, either from books, journals, news, or relevant online sources. The data was then analyzed descriptively.Results  -  The research results show that: first, based on the reading of Abdurrahman Wahid's humanistic da’wah, humanization was performed based on its role as a da’i, author, activist, or nationalist. Humanization was visible from the writings published in books or printed media,  the attitude of being aligned to the oppressed through speeches as his plea towards the oppressed, and the policy issued through revocation of President Instruction number 14 of 1967 replaced by President Decree Number 6 of 2000. Second, in the context of human rights abuse, humanistic da’wah could be performed through 4 (four) aspects: da’i, material, method, and mad’u. From the aspect of da’i, humanistic da’wah could be achieved by anyone. However, people with power and authority will have a more significant impact. The material in humanistic da’wah should be about pluralism, justice, equality, and affection (anti-violence). The methods used were policy advocacy, assistance for the victims, and a massive community awareness movement. While mad’u from humanistic da’wah means everyone, disregarding their sex, social class, race, religion, age, and disabilities.Implication – This result suggests improving the skills performance in da’wah strategy, messages, and methods related to social problems.Originality - This research is a complementary study of the previous works, which focus on Abdurrahman Wahid's role in performing da’wah based on his authority. This study emphasizes the four aspects of humanity which could be applied for da’i to accomplish the humanitarian phenomena.***Tujuan - Dua hal yang menjadi tujuan dari tulisan ini. Pertama, untuk mendeskripsikan dakwah humanistik Abdurahman Wahid. Kedua, membaca kontekstualisasi dakwah humanistik tentang Pelanggaran HAM.Metode - Artikel ini menerapkan fenomenologi Creswell dalam melihat fenomena pelanggaran HAM. Data diambil dari dokumen dakwah humanistik dan dakwah humanistik Abdurrahman Wahid, beserta kasus-kasus pelanggaran HAM yang terjadi, baik dari buku, jurnal, berita, maupun sumber online yang relevan. Data kemudian dianalisis secara deskriptif.Hasil - Hasil penelitian menunjukkan bahwa: pertama, berdasarkan pembacaan dakwah humanistik Abdurrahman Wahid, humanisasi dilakukan berdasarkan perannya sebagai da’i, penulis, aktivis, atau nasionalis. Humanisasi itu terlihat dari tulisan-tulisan yang dimuat dalam buku atau media cetak, sikap berpihak kepada yang tertindas melalui pidato-pidato sebagai pembelaannya terhadap yang tertindas, dan kebijakan yang dikeluarkan melalui pencabutan Instruksi Presiden nomor 14 tahun 1967 diganti dengan Keppres Nomor 6 Tahun 2000. Kedua, dalam konteks pelanggaran HAM, dakwah humanistik dapat dilakukan melalui 4 (empat) aspek: da’i, materi, metode, dan mad’u. Dari aspek da’i, dakwah humanistik dapat dilakukan oleh siapa saja. Namun, orang dengan kekuasaan dan otoritas akan memiliki dampak yang lebih signifikan. Materi dakwah humanistik harus tentang pluralisme, keadilan, kesetaraan, dan kasih sayang (anti kekerasan). Metode yang digunakan adalah advokasi kebijakan, pendampingan korban, dan gerakan penyadaran masyarakat secara masif. Sedangkan mad’u dari dakwah humanistik berarti semua orang, tidak memandang jenis kelamin, kelas sosial, ras, agama, usia, dan kecacatan.Implikasi – Hasil ini menyarankan peningkatan kinerja keterampilan dalam strategi dakwah, pesan, dan metode yang berkaitan dengan masalah sosial.Orisinalitas - Penelitian ini merupakan studi pelengkap dari karya-karya sebelumnya, yang berfokus pada peran Abdurrahman Wahid dalam melakukan dakwah berdasarkan otoritasnya. Kajian ini menekankan pada empat aspek kemanusiaan yang dapat diterapkan da’i untuk menyelesaikan fenomena kemanusiaan.